Past experience, cognitive frames, and entrepreneurship: some econometric evidence from the Indian pharmaceutical industry - Saradindu Bhaduri; Hagen Worch (Max Planck Institute of Economics, 2008)
The theoretical literature identifies three important entrepreneurial dimensions, namely discovering new opportunities, responsiveness to uncertainty, and coordination of a firm. In the empirical literature, past experience has been identified as having an important influence on organizational behavior. This literature, however, focuses predominantly on the impact of experience on new opportunities using a resource-based view and human capital perspective. In contrast, we draw upon the cognitive science literature to argue that past experience shapes an entrepreneur's cognitive frame, and, hence, influences entrepreneurship in a more holistic manner. We provide econometric evidence of the impact of past experience on all three entrepreneurial dimensions from the small scale Indian pharmaceutical enterprises.
Keywords: L26; M10; D83; 330; Entrepreneurship; Past experience; Cognition; Information and knowledge; Indian pharmaceutical industry; Unternehmer; Berufserfahrung; Kognition; Informationsverhalten; Pharmazeutische Industrie; Schätzung; Indien